Ultrasound Guided Central Chemotherapy Port Insertion by Surgeon in Cancer Patients. - Devkota, Mukti; Thakur, Binay; Chaudhary, Manish (Nepalese Journal of Cancer, 2022)
Purpose: The aim of the study is to report early experience in ultrasound guided central chemo port insertion by surgeons in cancer patients who required chemotherapy. Materials and methods: The procedure was carried out in operation theatre under local anesthesia with intravenous sedation. Linear high frequency ultrasound probe was used to visualize and cannulate left or right internal jugular vein in the neck. The reservoir was kept through a separate incision over anterior chest wall. Results: Fifty patients with mean age of 48 years underwent chemo port insertion. The indications were neoadjuvant, adjuvant and palliative chemotherapy in 30%, 58% and 12%, respectively. Cannulation was successful in 100% of cases. Two patients (4%) required port removal due to wound infection (one patient) and blockade (one patient). One patient (2%) had kinking of the catheter which required repositioning. Conclusion: Ultrasound guided central chemo port insertion by surgeons is a safe procedure with 100% success rate and minimal complications.